On the Role of Calcium in the Acute Release of Tissue-Type Plasminogen Activator and von Willebrand Factor from the Rat Perfused Hindleg Region - Tranquille, N; Emeis, J J (Thrombosis and Haemostasis, 1991)
The involvement of calcium in the release of tissue-type plasminogen activator (t-PA) and von Willebrand Factor (vWF) from vascular endothelial cells was studied ex vivo using a rat hindleg perfusion system. By adding either platelet-activating factor or bradykinin to the perfusing Tyrode solution, a rapid release of t-PA and vWF was induced. Extracellular calcium was required for the acute release of both glycoproteins as this release was totally abolished in the presence of EGTA. The calcium ionophore A-23187 induced (Ca-dependently) the release of both proteins, suggesting that Ca-influx was also sufficient to induce release. The absence of an effect of the calcium L-type channel blockers, verapamil and diltiazem, and of the calcium channel agonist BAY K-8644, suggested that endothelial voltage-operated calcium channels were not involved in release. Trifluoperazine, a calmodulin antagonist, significantly inhibited the induced release of t-PA and vWF, while the "intracellular calcium antagonist" TMB-8 had no effect. Lanthanum chloride (200 εM) inhibited the induced release of t-PA but not that of vWF. Our results suggest that Ca2+ influx is essential for the release of t-PA and vWF from the perfused rat hindleg.